2017
DOI: 10.4491/eer.2017.062
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photocatalytic oxidation of humic acids using Fe3+-Zn2+ co-doped TiO2: The effects of ions in aqueous solutions

Abstract: Photocatalytic oxidation in the presence of Fe-doped, Zn-doped or Fe-Zn co-doped TiO2 was used to effectively decompose humic acids (HAs) in water. The highest HAs removal efficiency (65.7%) was achieved in the presence of 500°C calcined 0.0010% Fe-Zn co-doped TiO2 with the Fe:Zn ratio of 3:2. The initial solution pH value, inorganic cations and anions also affected the catalyst photocatalytic ability. The HAs removal for the initial pH of 2 was the highest, and for the pH of 6 was the lowest. The photocatalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Various TiO 2 -based photocatalysts by metallic or/and nonmetallic ions doping and codoping have been successfully used for the degradation of organic pollutants [26][27][28][29][30]. Among various doping methods, nitrogen doping has been considered as one of the most encouraging due to comparable atomic size to oxygen and small ionization energy of nitrogen atom [31].…”
Section: •−mentioning
confidence: 99%
“…Various TiO 2 -based photocatalysts by metallic or/and nonmetallic ions doping and codoping have been successfully used for the degradation of organic pollutants [26][27][28][29][30]. Among various doping methods, nitrogen doping has been considered as one of the most encouraging due to comparable atomic size to oxygen and small ionization energy of nitrogen atom [31].…”
Section: •−mentioning
confidence: 99%
“…Metode lain yang efektif adalah codoping: logam, nonlogam, atau secara bersamaan logam-nonlogam. Co-doping ion Fe 3+ dan Zn 2+ pada TiO2 menghasilkan sifat fotokatalitik yang lebih baik dibandingkan dengan bahan yang didoping ion besi atau seng saja (Yuan et al, 2018). Contoh lain dari co-doping logam adalah TiO2 yang didoping dengan logam Fe dan Ni (Lin et al, 2017).…”
Section: Pendahuluanunclassified
“…The lower residual color after oxidation with H2O2/O3 as the H2O2/O3 ratio increased was attributed to the increased formation of OH radicals [20][21][22][23]. Other studies have reported increased H2O2/O3 ratios and biodegradability after wastewater treatment with O3 and H2O2 [24,25].…”
Section: Optimization Of H2o2/o3 Ratiomentioning
confidence: 99%